Formation and diagnostics levels of educational abilities of students in physical education. - Маракушин Андрій Ігорович (Andriy Marakushyn); Піддубний Олександр Григорович (Oleksandr Piddubnyi); Коновалов Володимир Володимирович (Volodymyr Konovalov); Кірпенко Віталій Миколайович (Vitaliy Kyrpenko) (Slobozhanskyi Herald of Science and Sport, 2015)
Purpose: specify and theoretical basis for the content of educational tasks methodical practice, as a means of diagnosing the level of formation and pedagogical skills of students. Material and Methods: the analysis of more than 20 references, 12 work programs in the discipline "Physical Education" HEI III–IV accreditation levels. Results: disclosed system of pedagogical skills, providing social and personal competence in the sphere of physical culture, which forms during the methodical practice through completing quests. Conclusions: this study allows a qualitatively new level to solve the issues of forming and diagnostics level pedagogical skills of students in physical education